Pembuatan Website UMKM Batik Apik Sebagai Media Pemasaran Dan Promosi - Gideon Setyo Budi Witjaksono; Achmad Danis Harjuna Putra; Agung Pambudi; Diva Dhotin Fajriyah; Jesika Juita Lumban Raja; Thariza Afriliya Putri (Fakultas Teknik Universitas Cenderawasih, 2023)
Batik is an Indonesian cultural heritage that has more than a hundred different motifs, even in every region throughout Indonesia has its own distinctive motifs. There are several batik motifs that are very popular among Indonesian people including mega mendung batik, parang batik, sogan batik, and keraton batik. Techniques in making batik itself vary every region and every motif. Batik making in Indonesia is popular with writing, stamping, printing, tie, and splashing techniques. The tie and splash technique is a technique that is easy to learn compared to other techniques, because it does not require special techniques in its manufacture. In East Java, precisely in Tlumpu Village, Sukorejo District, Blitar City, there are batik craftsmen who develop batik with splash and tie techniques. Website is one of the promotional media that can be used as an introduction, promotion, or sales medium of a product. The creation of a website for Batik Apik MSMEs in Blitar City aims to help analyze the potential of batik in Blitar City and become a promotional medium for MSMEs. The hope is that creating a website can help MSMEs in promoting their products and becoming a product sales platform.